2002
DOI: 10.1097/00000421-200202000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Late Adrenal Metastasis in Operable Non–Small-Cell Lung Carcinoma

Abstract: Treatment of early-stage (I, II, and some IIIA) non-small-cell lung cancer (NSCLC) is curative resection. Simultaneous isolated adrenal metastasis represents a dilemma. Although many studies addressing the management of adrenal metastasis diagnosed simultaneously with NSCLC have been published, only very few reports of late adrenal metastasis can be found in the literature. Our purpose is to discuss the management of solitary late (metachronous) adrenal metastasis from operable NSCLC based on published experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Retrospective and prospective research has failed to conclusively demonstrate a survival advantage. 14 Our patient received one course of induction chemotherapy and was noted to have a significant drop in the primary tumor standardized uptake value (SUV). Thus, given that in vivo litmus test, we would expect to achieve a survival improvement by administration of adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 91%
“…Retrospective and prospective research has failed to conclusively demonstrate a survival advantage. 14 Our patient received one course of induction chemotherapy and was noted to have a significant drop in the primary tumor standardized uptake value (SUV). Thus, given that in vivo litmus test, we would expect to achieve a survival improvement by administration of adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 91%
“…Data from the National Central Cancer Registry of China revealed that lung cancer accounts for the greatest number of cancer-related deaths and exhibits an increasing incidence and mortality trend in China ( 2 ). Non-small cell lung cancer (NSCLC) accounts for approximately 80–85% of lung cancer cases, and displays an aggressive phenotype with almost half of the patients presenting with metastases ( 3 ). Metastasis is the primary contributing factor to NSCLC-related mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Common sites of metastases for lung cancer are the nervous system (39%), bone (34%), liver (20%), and adrenal gland (8%) [5]. Isolated metachronous or synchronous adrenal metastasis is rare, with an estimated incidence rate between 1%-6% [6][7][8]. In the case of isolated adrenal metastasis, metachronous metastasis, lack of lymph node involvement, and disease-free interval are among the factors associated with better survival rates [7,9].…”
Section: Introductionmentioning
confidence: 99%